Impact of the Gatt Uruguay Round negociations on Turkish agriculture - Esin H. (The GATT and Mediterranean agricultural trade, 1997)
The recent developments in the international economy show that liberalisation will prevail in the world economy for the near future. Competition and market information are expected to be the dominant factors of the coming decade. Turkey consolidated all of the agricultural products to GATT with respect to reduction of tariffs and export subsidies. To non-product specific support or product specific domestic support was below the 'de minimis' level of support. However, Turkey reserved the right to derogate from the 'de minimis' provision in accordance with developments concerning the adoption of Common Agricultural Policy of EU. The tariff reduction commitments for the commodities considered strategic are kept at low levels and are due to high import taxes as well. In the agricultural sector it was established that more liberalised trade would improve the net trade position of Turkey for agricultural products. Turkish agricultural producers will benefit more than the consumers with the full implementation of the GATT 1994.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)